Understanding the structural, optical, and dielectric characteristics of SrLaLiTe1−x Mn x O6 perovskites - M. Z. M. Halizan (Nature Portfolio, 2021)
Abstract In electronic applications, good dielectric permittivity material has huge potential in the capacitive energy storage devices. Herein, in the present work the dielectric study of SrLaLiTe1−x Mn x O6 (x = 0.02, 0.04, 0.06, 0.08, and 0.10) double perovskites has been studied and discussed. These compounds were prepared through solid-state reaction method. All of the prepared compounds were confirmed to crystallized in monoclinic structure of P2 1 /n space symmetry with better crystallization when dopant concentrations increased until x = 0.08. The formation of Li–O–Te/Mn bonds in octahedral structures in all compounds were confirmed in this study. The existence of peaks at specific wavenumbers indicated vibrations of B–site cations’ bonds. When dopant amounts were increased from x = 0.02 to x = 0.08, there was an increasing trend of grains sizes formation in the compounds. The discussions on effects of grain sizes towards dielectric properties were included in this paper. Other important results and discussions comprised of the significant effects of dopant on the optical band gap (E opt ) and absorption frequencies of the compounds. The decreasing trend of E opt towards semiconductor range indicated the compounds’ promising potentials for optoelectronic device application.